Unlock. : Reading & writing skills. 1 (Cambridge: Cambridge University Press, 2014)
Unlock is a four-level academic skills course that combines thought-provoking video from Discovery Education(TM) with carefully scaffolded exercises and a fresh approach to critical thinking skills.
Unit 1. People; Unit 2. Seasons; Unit 3. Lifestyle; Unit 4. Places; Unit 5. Sport; Unit 6. Jobs; Unit 7. Homes and Buildings; Unit 8. Food and Culture; Unit 9. The Animal Kingdom; Unit 10. Transport.
student's book with unlock online workbook-- cover
A1 English profile-- cover
Keywords: English language -- Study and teaching -- Foreign speakers; English language -- Spoken English -- Study and teaching; English language -- Study and teaching -- Activity programs